Analisis kesulitan menulis permulaan pada peserta didik kelas I SDN 3 tugu kecamatan cihideung - Nurshinabani Suryana; Cece Rakhmat; Deni Chandra (COLLASE (Creative of Learning Students Elementary Education), 2024)
ABSTRACT Beginning writing is a writing skill that is taught to students in the early stages, namely in classes I and II. The aim of this research is to analyze the difficulty of beginning writing in class I students at SDN 3 Tugu, Cihideung District. This research uses descriptive qualitative research methods. The data collection techniques used by researchers are tests, observations and interviews. Based on the results of observations and interviews conducted by researchers regarding students who had difficulty writing at the beginning, the researchers analyzed 5 aspects of writing letters A-Z using uppercase and lowercase letters, writing words according to pictures, copying sentences correctly and accurately, and writing words and sentences using the imla/method. dictation 4 out of 6 students namely SN, SA, RMS, and RA could not write the beginning while AP and AY were quite able to write the beginning. There are 2 factors that cause students to have difficulty in writing beginnings, namely internal factors and external factors. Key words : writing, writing beginnings ABSTRAK Menulis permulaan merupakan kemampuan menulis yang diajarkan pada siswa di tahap awal yaitu dikelas I dan II. Tujuan dari penelitian ini ialah untuk menganalisis kesulitan menulis permulaan pada peserta didik kelas I SDN 3 Tugu Kecamatan Cihideung. Penelitian ini menggunakan metode penelitian kualitatif desktriptif. Teknik pengumpulan data yang digunakan oleh peneliti yaitu dengan tes, observasi, dan wawancara. Berdasarkan hasil observasi dan wawancara yang dilakukan peneliti mengenai peserta didik yang kesulitan menulis permulaan peneliti menganalisis 5 aspek menuliskan huruf A-Z menggunakan huruf kapital dan huruf kecil, menuliskan kata sesuai gambar, menyalin kalimat dengan benar dan tepat, serta menuliskan kata dan kalimat dengan metode imla/dikte 4 dari 6 orang peserta didik yaitu SN, SA, RMS, dan RA belum bisa menulis permulaan sedangkan AP dan AY cukup bisa menulis permulaan. Ada 2 faktor yang menyebabkan peserta didik kesulitan dalam menulis permulaan yaitu faktor internal dan faktor eksternal. Kata kunci : menulis, menulis permulaan